Corporate Social Responsibility And Stakeholder Engagement: A Case Study Of Arab Orient Insurance Company - Kanan, Suleiman Fawwaz (2012)
Nowadays, corporate social responsibility (CSR) is playing an important role in insurance sector to ensure social justice and moral practices.